O letramento nos anos finais do ensino fundamental à luz da Base Nacional Comum Curricular - Caetano, Amarildo Alves (2023)
This work seeks to answer the following question: What does BNCC propose regarding promotion of literacy work in the final years of Elementary School (EF) and what principles theoretical and methodological aspects are based on the proposal? It is in search of an answer to this question that this dissertation is focused on, pursuing the theme of BNCC and literacy in the final years of the EF. The objective is to reflect on the literacy proposal presented in the BNCC and its execution possibilities. To this end, it is based on BNCC studies (Brazil, 2018a), in addition to Freire (1989), Gil (2012), Kleiman (2008), Lemke (2010), Nóvoa (2022), Soares (2004, 2009) and Elicker (2019). In relation to the proposed objectives, the reflect on the literacy proposal for the Final Years of EF in light of the BNCC and the theoretical and methodological principles mobilized in the conception of this dissertation, we ratify that the research is understood as exploratory, as it focuses on the theme of literacy in BNCC with a view to better delineating and understanding it. To this end, the research presented here involves three major steps, namely: 1) survey of the literacy theme within the scope of BNCC, more specifically, with regard to the proposal for the Final Years of the EF; 2) search for principles and theoretical foundations that support the BNCC proposal; 3) relationship between proposal for literacy work at BNCC and the contemporary theoretical foundations in around the theme to compose a general picture of the theme, with an illustration of a work applied in an EF class in a public school in the State of Rondônia in which we act. The results allow us to affirm that the BNCC really is a basic document, essential and fundamental to progressively organize skills that lead students to fully develop reading, writing and multiplicities skills literacy of textual genres.